Eksistensi dan Peran Badan Arbitrase Nasional Indonesia Surabaya Sebagai Wadah Penyelesaian Sengketa Bisnis - Mariana Mugiono; Astrid Athina Indradewi (Amandemen: Jurnal Ilmu pertahanan, Politik dan Hukum Indonesia, 2024)
Increased activity in the business sector has led to competition, which has led to business disputes between business actors. Arbitration is a form of non-litigation dispute resolution with confidential, fast, simple, and measurable costs. This research uses a normative-dogmatic judicial research method with a statutory and regulatory approach and a conceptual approach. It is hoped that the presence of BANI Surabaya will be able to play a significant role in answering the needs of business actors in a non-litigation manner, especially in the city of Surabaya and its surroundings. The majority of dispute completions completed by BANI Surabaya are construction projects involving technical matters. The diversity of backgrounds and experiences of the arbitrators at BANI Surabaya can complement the results of the decisions made. BANI Surabaya has a role in administering the settlement process through arbitration based on applicable provisions.